FEEDING HABITS AND SYMBIOTIC RELATIONSHIPS OF THE CRAZY ANT Nylanderia fulva WITH OTHER ARTHROPODS. - ZENNER DE POLONÍA, INGERBORG; RUIZ-BOLAÑOS, NHORA (Revista Colombiana de Entomología, 1985)
In order to have a solid basis for control studies of the crazy ant this work was carried out during 1980 and 1981 at "Patio Bonito", Municipio Anapoima, Cund. In spite of not causing direct damage to the vegetation of the invaded areas, Nylanderia fulva (Mayr) (Hymenoptera: Formicidae, Formicinae) is responsible for a series of problems due to its high populations. The feeding habits were determined by observing the behavior of the workers in relation to homopteran insects, the prey taken to the nests, and the food found in them. The relationships with other arthropods were studied by surveying areas free and invaded by the insect and observing some relations in detail. The results indicate that the diet of N. fulva is composed of two parts: a liquid one, the honeydew secreted by sap-sucking homoptera, which attack every kind of vegetation, and a solid one made up of animal protein, procured by predation on insects, spiders, and even higher animals. The ant was found associated with 28 species of Homoptera, within 7 families. The ant obtains from them the honeydew and at the same time protects them against natural enemies and adverse environmental conditions transport them and install them on the hosts. To obtain the solid part of the diet, the ant shows a clear predatory action on insects, excepting Homoptera, and other arthropods. The most notorious influence of N. fulva as a displacement force was upon other ants; it seems that N. fulva uses the immatures of soil-inhabiting ants as proteic food for the brood. Among the displaced species, the leafcutting ants, Atta spp., a fire ant, Solenopsis geminata (F.), and Azteca spp. stand out. A reliable índex of the absence of N. fulva in a coffee plantation is the presence of the ant Camponotus senex (F. Smith).